AKIBAT HUKUM PIDANA TERHADAP SELEBGRAM YANG MEMBERIKAN INFORMASI TIDAK BENAR TERKAIT ENDORSEMENT PRODUK DI MEDIA SOSIAL INSTAGRAM - I Gusti Ayu Jatiana Manik Wedanti; Pande Komang Sri Agurwardani; I Made Suastika Ekasana (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This research was conducted to find out how theconsequences of criminal law for celebrities who promote products that harm consumers by conveying incorrect information through Instagram social media. The formulation of the problem in this study is what is the celebrity information that can be said to violate the law in order to endorse products on social media. What are the consequences of criminal law on celebgrams that provide incorrect information regarding product endorsements on Instagram social media. This research uses normative research methods. The results show that in carrying out celebrity endorsement activities, it is prohibited to provide inaccurate information regarding the information on the products being traded. In the Crime of Participation Deelneming, the position of the program in promoting products according to the requests of online traders is as a person who is ordered to commit a criminal act (Pleger). Criminal liability can only be asked to the person who ordered it (Doen Plegen), namely online traders. In this study, there was also no specific arrangement regarding the celebrity in making endorsements. The existing arrangements only ensnare business actors so that those who can take responsibility for mistakes are business actors who produce products.